Parental roles and strategies in career planning for employed persons with disabilities - Kalaw, Jerome S.; Magtoto, Frances Olivia M.; Olegario, Lizamarie Campoamor; Oael, Irene C.; Arzadon, Maria Mercedes E. (Quezon City College of Education, University of the Philippines Diliman, 2019)
This qualitative study examined the context in which parents whose children with disabilities have successfully been employed. If focused on the parental roles played during the career planning of their children with disabilities, and strategies used to overcome challenges to allow their children to be employed persons with disability. By looking into parental involvement specific to career planning of PWDs, an emerging framework is proposed. In-depth interviews conducted traversed the childs early childhood, formal schooling and transition to work, and employment. Three parents representing different socio-economic classes (from upper to lower-middle class) participated in the study. Each of them had a child diagnosed with either autism or intellectual disability. Identified themes were that: (1) The parents guided their children through early school years up to career planning - the father being the financial provider while the mother focused on childcare; (2) They provided academic and psychosocial support by becoming their childs tutor and behavior coach, liaising with training providers, and being social change agent; (3) Parents sought the help of a professional such as Job Coach and other agencies that could help their children to have career opportunities; (4) The mothers studied Special Education to understand their childrens needs and equip themselves with skills to provide academic and psychosocial support that helped in their childrens career planning; (5) Connections and linkages enabled them to find possible career opportunities for their children.
Thesis
Includes bibliographical references.
Keywords: Parents of children with disabilities -- Philippines; People with disabilities -- Vocational guidance -- Philippines; People with disabilities -- Employment -- Philippines